Food from peace: breaking the links between conflict and hunger - Messer, Ellen; Cohen, Marc J.; D'Costa, Jashinta (International Food Policy Research Institute, 1998)
In this paper, Ellen Messer, Marc J. Cohen, and Jashinta D'Costa show how hunger is often a direct result of violence ... [and] how hunger can reciprocally cause conflict... The authors call for including conflict prevention in food security and development efforts, as well as new linkages between food security and development on the one hand, and emergency relief on the other-- Foreword.